Wars, fought and unfought : China and the Sino-Indian border dispute - Balazs, Daniel (Nanyang Technological University, 2021)
When do Chinese leaders choose to fight and when do they want to avoid direct military engagement in frontier disputes? The question arises because China fought a war with India in 1962, clashed with the Soviets in 1969 and invaded Vietnam in 1979 over territorial concerns. In 1986 87, however, Sino Indian military tension on the disputed border subsided without a direct clash. China’s conduct is puzzling because the extent of force used by it does not always correspond with the challenge posed by the disputant—Indian fence building in 1967 led to Chinese attacks while similar actions in 1986 invited only limited measures. I argue that the threat environment faced by the state and its leaders is the most important factor that influences China’s propensity to use direct or limited force in territorial disputes. The more threatening the environment, the higher the level of force China is likely to use. China is most inclined to use direct force against a territorial disputant when it faces high level of external and internal threats at the time of the border crisis. Under these circumstances, China prefers to use direct force to reduce the external and internal threats. China is most likely to engage in military posturing against a territorial disputant if external threat is low and internal threat is high. This is a hybrid situation in which the leader needs to boost elite unity without antagonizing the great powers, hence the reason for military posturing. China is likely to make concessions in territorial disputes when it faces high external and low internal threats. In this setting, the leader enjoys the support of the political elite and can initiate negotiated territorial settlements without being charged with selling out the motherland. China is likely to delay the resolution of border disputes when external and internal threats are both low. Without foreign or domestic pressures, the leader is likely to choose the least costly way of maintaining the state’s territorial claims: delaying the resolution.